SEX RATIO AND AGE STRUCTURE PATTERNS OF ASIAN ELEPHANTS FROM PENINSULAR MALAYSIA REVEALED BY NON-INVASIVE SURVEYS - K. V. Karuppannan; K. A. Mohamed; M. F. A. Abdul-Razak; N. F. D. Ahmad-Tahir; N. A. Mohd-Naim; C. Keliang; S. Yaakop; J. E Maldonado; B. M. Md-Zain (Journal of Animal and Plant Sciences, 2020)
An effective conservation and management plan of Asian elephants in Peninsular Malaysia relies on understanding the population biology and ecology of the species. Since molecular genetic tools have been developed and widely used for elephant conservation, the Malaysian Department of Wildlife and National Parks (DWNP) aimed to obtain estimates of population size, individual identification and sex specific gene flow among elephant populations in Taman Negara National Parks (TNNP) in line with one of the long-term goals in the National Elephant Conservation Action Plan (NECAP). In this study, we apply non-invasive molecular techniques to sex Asian elephant faecal and we combine it with measurement of bolus dimensions to get reliable baseline information on sex ratio as well their age structure in TNNP, Peninsular Malaysia populations. Two Y chromosome specific fragments (SRY1 and AMELY2) and one X chromosome specific fragment (PLP1) were used to determine the sex of the elephants that were detected during our surveys in the TNNP study locations. A total of 217 fresh faecal samples from 31 sampling sites and measurements of each bolus circumference were analysed. Faecal samples from 10 elephant individuals of known sex from the National Elephant Conservation Centre (NECC), Kuala Gandah were included as controls. We identified 86 males and 131 females in TNNP via molecular sexing approach. In addition, to estimating the sex ratio in TNNP, we also categorized the different sexes into three different age classes by measuring mean of bolus circumference. Neonates/juveniles (Class 1) and sub-adults (Class 2) were composed of approximately an even number of males and females. However, our results of sexing, boli from adults (Class 3) revealed a lower number of males with 40 individuals compared to 84 females. This female biased sex ratio in adults could be due to poaching pressure on male adults around the study areas. Alternatively, we could have failed to detect more males because bulls are known to be more solitary and roam further in deeper forest areas away from their matriarchal herds and far from our sampling locations during our surveys. Despite these potential issues with detection of bulls, this study provided reliable information on the sex ratio pattern and age structure of free roaming elephant populations in TNNP. This information provides valuable scientific based management tools for DWNP as well policy makers in order to make decisions for future elephant conservation management plans in TNNP.
Keywords: Asian elephant; XY chromosome-specific markers; bolus circumference; age structure; poaching